Merger externalities in oligopolistic markets - Klaus Gugler; Florian Szücs (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We quantify externalities on profitability and market shares of competing firms in oligopolistic markets through the transition from an n to an n - 1 player oligopoly after a merger. Competitors are identified via the European Commission's market investigations and our methodology allows us to distinguish the externality due to the change in market structure from the merger effect. We obtain results consistent with the predictions of standard oligopoly models: rivals expand their output and increase their profits, whereas merging firms are negatively affected. This indicates that on average the market power effects of large mergers outweigh the efficiencies.
Keywords: L13; L40; G34; 330